Macromycetes of the Palace Park in Poznań-Radojewo (Wielkopolska Region, Poland) - Anna Kujawa (Acta Mycologica, 2020)
This work aimed to present the diversity of fungal species in the Poznań- Radojewo park. It was characterized based on literature data, unpublished master’s theses, the authors’ data, as well as data collected during two mycological trips organized by the Mycological Section of the Polish Botanical Society. Between 1980 and 2017, as many as 333 species of macromycetes have been found within the park in Poznań-Radojewo (among them 19% are rare and endangered), including eight protected species (Mitrophora semilibera, Morchella esculenta  (var. esculenta and var. umbrina), Geastrum corollinum, G. fornicatum, Hericium coralloides, and Myriostoma coliforme), as well as two species new to the Polish mycobiota: Psathyrella bipellis and P. larga. The park in Poznań-Radojewo is very important for maintaining a high species diversity of fungi within the city of Poznań. During revitalization works, it is of paramount importance to take the needs of rare, threatened, and protected species under consideration and to preserve the natural character of plant communities. It is also vital to ensure the presence of coarse woody debris at different decomposition phases, which serves as an important substratum type for rare fungi.